PENGARUH PERMAINAN BERBASIS KEARIFAN BUDAYA LOKAL TERHADAP PERILAKU KEMAMPUAN KONSENTRASI BELAJAR SISWA TAMAN KANAK-KANAK DI HUNIAN TETAP CANGKRINGAN SLEMAN YOGYAKARTA - , RHYANMITA NARETA ROZA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Merapi eruption that occurred in 2010 in Sleman psychological impact on children who demonstrated a decrease in ability to concentrate on studies. Concentration of poor study will disrupt and impede the development of the child to complete the task. One response to a decrease in the concentration of study after the eruption of Merapi is local cultural wisdom games Objective: This study aimed to identify effect games of local cultural wisdom to concentration ability behavior of kindergarten student at dwelling Cangkringan Sleman. Method: The study was quasi-experimental with pre-test and post-test control group design. The study carried out on February-Mei 2014. Sample was children age 5-6 years old from 2 kindergarten near the shelter that consist of 25 children intervention group and 25 children control group. This study uses an instrument Concentration Ability Behavior and data of this study analized with parametric t-test Result: There was significant differences between intervention group and control group. Before intervention of local cultural wisdom games, concentration ability behavior score 52.64 ± 7.30 and 53.44 ± 6.82. After intervention, concentration ability behavior score 71.64 ± 5.47 (p = 0.691) and 54 ± 6.29 (p = 0.016). Conclusion: There was effect of games of local cultural wisdom to concentration ability behavior of kindergarten student at shelter in Cangkringan in Sleman.